Analysis Of The Effectiveness Of Accounting Information Systems At PT Pos Indonesia Pringsewu Branch - Sunarmi; Sofie Amalia; Juliana (Institute of Computer Science (IOCS), 2022)
An accounting Information System is a system that controls every activity that is in the responsibility center area. We can see the role of the accounting information system at the time of reporting responsibility accounting. A good accounting information system will produce a good accountability report. PT. Pos Indonesia (Persero) Pringsewu is a branch of a state-owned logistics company that now has more than forty branch offices spread across Lampung Province. However, these branch offices do not compile their own financial reports but are only profit responsibility centers that periodically report accountability accounting reports to the auditing office (Lampung regional office). This study aims to determine the role of accounting information systems in the effectiveness of branch office accountability accounting reporting. This study used the descriptive qualitative method. The results showed that the accounting information system at PT. Pos Indonesia (Persero) Pringsewu has played a good role, especially in the effectiveness of its accountability accounting reporting. It is hoped that it is necessary to improve the quality of existing human resources in the company because it also affects the effectiveness of the implementation of the existing system.